Dinâmica urbana e pichação: entre preto fosco e tons de concreto há quem prefira outras cores - Glauce Cristine Ferreira Santos Viegas (2014)
The relationships between identities and places in the city are made notorious in approach to the phenomenon of pichação and can go beyond this dimension, since the circuit permeates different ages, socioeconomic classes, varied behaviors and assimilation. What is worrying that little scenario should be reparations of its concrete interventions in concrete. More attention than the physical and moral violation, abuse of power and strengthening of social stigmas mutually conferred. Forms of oppression and aspects of otherness thus are elements that invigorate discussions on the practice by the assumptions of identity and its connections to social interactions and power relations, which in the urban context, everywhere, can be done by dominant and dominated. My goal in this research was to characterize, in terms of identity and topographical, urban dynamics related to the pichação circuit in Belo Horizonte. In an attempt to explain this understanding. In an attempt to explain this understanding I insert interdisciplinary theoretical approaches and I wonder about the relations between the thematic identity and places in the city. From the interpretive paradigm and qualitative methodological strategy of primary and secondary data on the circuit of pichação in Belo Horizonte, which contemplated interviews with representatives of the municipality, society and pichação in Belo Horizonte were collected, in addition to official documents and direct and indirect observations places in the city, contemplated by the Pampulha Architectural Complex; Lagoinha Complex, and the Santa Tereza Viaduct. After organizing the material was analyzed according to the elements of discourse analysis in its french side, among whom were also aggregated iconographic order to complement the analysis of the reports when those referred to the places of research data. The main results suggest that urban dynamics related to graffiti in BH is characterized by organizational control practices and resistance and identity and topographical appeals dimanantes of the strategies to combat graffiti from city program Respect Movement by BH The various interactions identified correspond to organizational arrangements between sociourbanos agents, which, in different positions, order and subvert the organization of the city. Discourses vary, so at different points of view, in that particular prism combat graffiti, through actions revitalization of urban space; speeches about good and public and private equity, and testing control of the city and its citizens. From another angle, the practices of resistance to city planning, not in a horizontal process of popular participation are oriented in speeches that disregard the preference of other groups in society, securing the written street through town and by individual walls, for example. Furthermore, it is concluded on the intensification of the insurgency along the taggers and other individuals representing the practice in the city, which is formed by the arbitrariness of municipal public administration and before alteritária decay, characteristic of contemporary societies.